2019
DOI: 10.1096/fj.201800489r
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale analysis in CD38 −/− mice unveils major prefrontal cortex dysfunctions

Abstract: Autism Spectrum Disorder (ASD) is characterized by early onset of behavioural and cognitive alterations. Low plasma levels of oxytocin have also been found in ASD patients and recently, a critical role for the enzyme CD38 in the regulation of oxytocin release was demonstrated. CD38 is important in regulating several Ca2+ dependent pathways, but beyond its role in regulating oxytocin secretion, it is not known whether a deficit in CD38 expression leads to functional modifications of the prefrontal cortex, a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…would be consistent with elevated levels of anxiety and emotional reactivity to negative events that have been seen in mice with deletion of the CD38 gene (Martucci et al, 2019). Exploratory whole brain analyses showed main effects of neuroticism on regions that are considered part of the default mode network, such as the temporoparietal junction, precuneus, and sgACC (Menon, 2011;Li et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…would be consistent with elevated levels of anxiety and emotional reactivity to negative events that have been seen in mice with deletion of the CD38 gene (Martucci et al, 2019). Exploratory whole brain analyses showed main effects of neuroticism on regions that are considered part of the default mode network, such as the temporoparietal junction, precuneus, and sgACC (Menon, 2011;Li et al, 2014).…”
Section: Discussionsupporting
confidence: 67%
“…Reduced levels of oxytocin have been found in ASD patients, and CD38 is a vital enzyme that controls oxytocin production. A CD38 −/− mice study showed abnormal development of the cortex and impaired synaptic plasticity in the prefrontal cortex region with impaired social and emotional responses 108 (Table 1). Genetic variations in the 1A gene of the arginine vasopressin receptor (AVPR1A) were linked to autism.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…This reduction in cADPR levels in these brain areas led to a reduction of oxytocin and vasopressin release, explaining the observed defects in maternal nurturing and social behavior characteristics of CD38 KO mice [39]. This effect is not limited to the posterior pituitary hormone family of neurotransmitters since norepinephrine, serotonin and the dopamine metabolites dopac and homovanillic acid are strongly increased in prefrontal cortex from CD38 KO mice [40]. CD38 KO mice also had reduced dopamine release in the nucleus accumbens [41].…”
Section: Physiological Role Of Cd38 Enzyme Function In the Brainmentioning
confidence: 92%